Does the human developmental factors of the parents sustain the learning quality of the undergraduates? - A critical Analysis - Aditya Prakash; R. Hariharan; Gynendra Kumar Rout (Sustainable Futures)
The aim of this research is to analyze the impact of the Human Development Index on the quality of education of graduate students in Lucknow district, Uttar Pradesh. In this survey method, totally of 688 Undergraduates are randomly selected. As recorded by the graduate students there are 659 parents have the lowest level of HDI values 26 moderate and only 3 parents have higher HDI. The lowest HDI values has shown the lack of sustainable life orientation of the parents who have destitute living conditions. The correlation analysis has showed that the Health Index, Education Index, Income Index and Human Development Index of parents have negative relationship with the learning quality. Similarly the regression values has no influence of the indices on leaning quality.